Experimental Investigation on Thermal Performance of Desiccant Coated Heat Exchanger in Series with Heat Exchanger - Cao Wei; Ge Tianshu; Zheng Xu; Dai Yanjun; Wang Ruzhu (Zhileng xuebao)
A desiccant coated heat exchanger can handle sensible load and latent load simultaneously; however, owing to the influence of adsorption heat, the heat load and moisture load treatment is not synchronous, and the ability to handle sensible load is insufficient. Based on this, another sensible heat exchanger is added in-series for the air secondary treatment. An experiment setup was built to test the dynamic performance of two heat exchangers connected in-series. In addition, the influence of the main operation parameters including the water temperature, air temperature, air humidity, and air velocity on the system performance are analyzed. The results show that a sensible heat exchanger can clearly improve the ability to handle sensible load, particularly during the beginning period, and the cooling capacity of the system is also significantly improved. Moreover, under the experiment conditions, the cooling and heating water temperatures can both improve the cooling capacity and COP, a higher air temperature and relative humidity ratio lead to a better performance, and a lower air velocity is helpful for increasing the average dehumidification capacity and the effective dehumidification time.